THE IMPORTANCE OF TRANSLATING AND INTERPRETING STUDIES TOWARDS STUDENT’S SPEAKING SKILL - Suhendar Suhendar (Journal of English Language and Literature (JELL), 2017)
Principally, the objective of this research is to find out the result of achievement of student’s speaking skill through the performance of translation and interpreting studies. In view of that, this research constitutes one of teacher’s best endeavors to recognize the attainment of student’s speaking skill as the prerequisite for them to get a highly qualified competency for their carrier in the future. Hence, the objective of education for which the students pursue in the university can be accordingly achieved. The achievement of students speaking skill in the society is very important due to the fact that many kinds of world-class business opportunities need a qualification of competency-based speaking skill. The steps of improving the students speaking skill through translating and interpreting study are namely understanding linguistics, socio linguistics and psycho-linguistics and vocabulary as well.